Pemberdayaan Ekonomi Masyarakat melalui Pengelolaan Objek Wisata Air Terjun Waylalaan di Pekon Kampung Baru Kecamatan Kota Agung Timur Kabupaten Tanggamus - Ahmad Riansyah; Faizal Faizal; Mansur Hidayat; Zamhariri Zamhariri; Sri Wahyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Pekon Kampung Baru is a pekon with the majority of people having livelihoods as farmers, so that the community's economy only relies on agricultural products to meet their needs. Pekon Kampung Baru has tourism potential in the form of a waterfall that can be managed so that it becomes a competitive tourism to attract tourists and have an impact on improving the economy of the Pekon Kampung Baru community with a planned and structured management pattern so that the potential utilised can develop optimally. In this study the authors used methods of collecting, processing, and analysing data with the type of research that is qualitative. The data collection includes interviews, observation, and documentation. The process of community economic empowerment through the management of the Way Lalaan waterfall tourist attraction, there are several stages in it, namely the capacity building stage, and enrichment. the conclusion of managing the Way Lalaan waterfall tourist attraction through the Way Lalaan Tourism Awareness Group is carried out with the following four stages, namely: Capacity Building, Institutional Strengthening, and Provision of Economic Business Facilities.